Effects of Growth Regulators Produced by Methylobacterium radiotolerans Ed5-9 and Crude Antimicrobial Agents Extracted from Streptomyces TM32 on Tissue Culture of Gymnema inodorum (Lour.) Decne. - Sarin, Siripun; Nakaew, Nareeluk; Chidburee, Aphichat (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 3 (2018): July-September 2018DO - 10.14456/nujst.2018.4, 2018)
Since the demand for medicinal plant in pharmaceutical industries as plant based raw materials is becoming greater in quantity, the propagation of large number of plant in relatively short period of time can be produced by tissue technique. However, one of the most serious problems of plant cell and tissue culture is microbial contamination. The effectiveness of crude plant growth promoting substances extracted from the isolates Methylobacterium radiotolerans ED5-9 (MIAA) and the Streptomyces TM32 (SCE) for plant growth and development on tissue culture of the G. inodorum , a medicinal plant widely used in Northern Thailand, was therefore investigated. After incubation for 4 weeks, cooperation of the MIAA and SCE in basal liquid medium condition showed significantly ( p < 0.05) higher increase in the length of shoot tip of explants than those semi-solid medium. High levels of IAA from both the M. radiotolerans ED5-9 and the Streptomyces TM32 caused reduction of shoot growth and root development when compared with the control treatment consisted of the MIAA alone. The measurement of greenness of leaves (SPAD readings) showed lower values from the liquid medium than that of the semi-solid treatments. The active antioxidant activity and total phenolic content accumulated in the plantlets of G. inodorum in semi-solid cultured plantlets were at a higher level than those in liquid treatment. Moreover, all these of SCE treatments, which contained crude antifungal agents, had no microbial contamination appearance during incubation. This study suggested that beneficial effects of the growth promoting substances producing, particularly IAA less than 0.01 mg/L, from both the M. radiotolerans ED5-9 and the Streptomyces TM32 or even from the M. radiotolerans ED5-9 alone might have potential for use as bio-fertilize or anti-microbial agent on micro-propagated Chiang Da, G. inodorum , in the semi-solid medium condition. Keywords: Gymnema inodorum ; Methylobacterium radiotolerans ; plant growth promoting substances; Streptomyces ; tissue culture